PENGARUH GAYA KEPEMIMPINAN DAN PROMOSI JABATAN TERHADAP KOMITMEN KERJA BIDANG TATA RUANG KOTA SEMARANG - NURHIDAYAH, EVINTA AMALIA (JURNAL CAPITAL : Kebijakan Ekonomi, Manajemen dan Akuntansi, 2023)
Abstract. Leadership style and promotion are factors that can influence work commitment decisions. The leadership style experienced by employees will have an impact on the agency which will ultimately result in work commitment. Job promotion is also an important factor in increasing employee work commitment. This research aims to determine whether or not there is an influence of leadership style, incentives and job promotions on work commitment in the Semarang City Spatial Planning Sector. The population in this study were all employees of the Semarang City Spatial Planning Sector, totaling 39 employees. Using the census/sample method via questionnaire. Primary data was obtained from a questionnaire with 39 respondents. Data were analyzed using multiple linear regression equations, hypothesis testing (t test and f test) and coefficient of determination (R2). Leadership style has no significant effect on work commitment in the Semarang City Spatial Planning Sector. This is proven by a significant test which has a significance level of 0.160 > 0.05. Thus, the first hypothesis in this research is accepted and promotion has a significant effect on the work commitment of the Semarang City Planning Service. This is proven by a significance test which has a significance level of 0.001 < 0.05. Thus the first hypothesis in this research is accepted. Suggestions from the results of this research are that agencies pay more attention to job promotions which have the greatest influence on commitment, so that employees can work harder and be committed to achieving maximum work goals and results in accordance with the targets determined by the agency.